Jana Sterbak - Life-size - Dinkla, Söke 1962-; Tabassomi, Nina 1977- (Verlag für moderne Kunst, 2017)
The Galerie im Taxispalais is showing the first comprehensive retrospective in Austria of work by Czech-Canadian artist Jana Sterbak (*1955 in Prague, lives and works in Montréal). Examination of the body and identity, materiality and the processual plays a key part in Sterbak?s multifaceted oeuvre. In her sculptural, performative, photographic and film works she generates both direct and indirect references to the conflicts of the human subject in the context of contemporary society, testing its extension as well as limitations, indicating its vulnerability as well as resilience, and sounding out the transition from the intimate to the public sphere. At the same time, subversive and ironic-humorous echoes resonate in Sterbak?s works, helping her to uncover social conventions, constraints and role clichés.00Exhibition: Galerie im Taxispalais, Innsbruck, Austria (03.12.2016-12.02.2017)
Dieser Katalog erscheint anlässlich der Ausstellung Jana Sterbak. Life-Size, Galerie im Taxis-Palais, Innsbruck (03.12.2016-12.02.2017) und im Lehmbruck-Museum, Duisburg (11.03.2017-11.06.2017)
Keywords: Sterbak, Jana -- 1955-; Geschichte 1978-2016; Videokunst; Zeichnung; Performance -- Künste; Fotografie; Installation -- Kunst; Ausstellungskatalog -- Galerie im Taxis-Palais -- 03.12.2016-12.02.2017 -- Innsbruck; Ausstellungskatalog -- LehmbruckMuseum -- 11.03.2017-11.06.2017 -- Duisburg